Look what i can do! a lift the flap book - Siewert, Pauline (Windmill Books New York, 2010)
This vibrant story encourages children to discover their unique talents and abilities. Through playful illustrations and simple text, kids are invited to celebrate their skills, whether it's dancing, singing, or building. The book promotes self-confidence and the joy of self-expression.